A Molecular Dynamic Simulation of Hydrated Proton Transfer in Perfluorosulfonate Ionomer Membranes (Nafion 117) - Hong Sun; Mingfu Yu; Zhijie Li; Saif Almheiri (Journal of Chemistry)
A molecular dynamic model based on Lennard-Jones Potential, the interaction force between two particles, molecular diffusion, and radial distribution function (RDF) is presented. The diffusion of the hydrated ion, triggered by both Grotthuss and vehicle mechanisms, is used to study the proton transfer in Nafion 117. The hydrated ion transfer mechanisms and the effects of the temperature, the water content in the membrane, and the electric field on the diffusion of the hydrated ion are analyzed. The molecular dynamic simulation results are in good agreement with those reported in the literature. The modeling results show that when the water content in Nafion 117 is low, H3O+ is the main transfer ion among the different hydrated ions. However, at higher water content, the hydrated ion in the form of H+(H2O)2 is the main transfer ion. It is also found that the negatively charged sulfonic acid group as the fortified point facilitates the proton transfer in Nafion 117 better than the free water molecule. The diffusion of the hydrated ion can be improved by increasing the cell temperature, the water content in Nafion, and the electric field intensity.